Parental Financial Socialisation and Child’s Gender - Ndou, Adam (International Journal of Economics and Financial Issues, 2023)
Parental financial socialisation is impactful to children’s development of healthy financial behaviour. This study determined the difference in parental financial socialisation across child’s gender in rural and low-income areas in South Africa. Parental financial socialisation was measured through parental financial behaviour, parental financial monitoring, parental financial discussion, parental financial communication, and parental financial teaching. Quantitative research was used in this study. The research design adopted is the survey design, a non-experimental research design. Self-administered questionnaire was used to collect data from young black African adults in Fetakgomo Tubatse and Intsika Yethu municipalities because they are the most rural and low-income areas in South Africa. Descriptive statistics and T-tests were performed to test hypotheses. The results showed that there is no significant difference in parental financial socialisation according to the child’s gender. Thus, this study does not support the notion that male children are more likely than female children to receive parental financial socialisation as argued in literature. This study recommended that financial educators and government must come up with financial programmes where issues of gender and financial socialisation will be addressed.